Optimal sizing model of battery energy storage in a droop-controlled islanded multi-carrier microgrid based on an advanced frequency droop model - Abouzar Samimi; Mehdi Nikzad; Adel Zakipour (Scientific Reports)
Abstract This paper introduces an optimal sizing approach for battery energy storage systems (BESS) that integrates frequency regulation via an advanced frequency droop model (AFDM). In addition, based on the AFDM, a new formulation for charging/discharging of the battery with the purpose of system frequency control is presented. The studied MG system that consists of PV units, a diesel generator (DG), a combined heat and power (CHP) unit, a gas boiler, and a BESS is designed to meet the consumers’ thermal and electrical load requirements as well as system frequency regulation. In the proposed optimization model, the net present value of expansion planning costs (EPC) over the project lifetime should be minimized according to the capacity of installed BESS. The EPC consist of four components including, (i) MG operation cost pertaining to the DG, CHP units and gas boilers, (ii) value of lost load, (iii) BESS investment cost, and (iv) replacement cost of BESS, recognizing its shorter lifetime relative to the project’s lifespan. The effectiveness of the proposed method and its advantages compared other methods are demonstrated via a case study simulation. Compared to the conventional frequency droop characteristic, the utilized AFDM can reduce the total EPC while a broader range of power/frequency control capabilities of the BESS is achieved to regulate the frequency in a desired band. Furthermore, the paper examines the impact of the AFDM on the selection of battery technology.